Rock Island, Trinidad, B.W.I. - (:unkn) unknown (Yuille, 2011)
Rock Island is a small island in Trinidad and Tobago, part of the Five Islands group of islands. It is located in the Gulf of Paria, approximately 2 kilometres off the main island of Trinidad from Point Gourde. Of the "Five Islands", which are actually made up of six different islands, Rock Island is the second smallest (after Craig Island) and the most western of the group.
Colour: Black and white; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Paria, Gulf of (Venezuela and Trinidad and Tobago); Islands--Trinidad and Tobago; Bodies of water--Trinidad and Tobago; Vacation homes--Trinidad and Tobago; Dwellings--Trinidad and Tobago; Architecture--Trinidad and Tobago; [1901]; Five Islands, The (Trinidad and Tobago)